THE FREQUENCY OF OCCURRENCE AND PATHOMORPHOLOGICAL FEATURES OF UTERINE FIBROIDS IN WOMEN, DEPENDING ON THE AGE - Alibekov O.O (Scholar Express Journals, 2025)
This article is based on the study of the etiology, pathogenesis, pathomorphology, diagnosis and treatment of uterine fibroids. Among the many studies devoted to this problem, in our opinion, the epidem iology of this disease is insufficiently studied. Thus, in a number of studies it was noted that in some age groups of the female population living in different climatogeographic zones of the country, there are differences in the frequency of detection offibroids, risk factors and age periods in which the first clinical manifestations of the disease are noted. In this regard, further collection of materials on this pathology, analysis and search for new clinical manifestations, assessment of pathomorphological risk factors for the development of the disease not only clarify and expand existing ideas about the pathogenesis of fibroids, but also allow us to establish new data to improve the effectiveness of treatment, diagnostics, and the quality of treatment of this category ofpatients.
Keywords: pathomorphology; fibroids; pregnancy; woman